Basic study for drive mechanism with synthetic fiber rope – investigation of strength reduction by bending and terminal fixation method. (1st February 2016) - Horigome, Atsushi; Endo, Gen
Abstract : In this study, we investigate physical properties of synthetic fiber ropes for drive mechanism. First, we carry out experiment about the relation between tensile strength and bending ratio D / d, where D is pulley diameter and d is rope diameter. Although it is widely known that a metal wire rope gets strength reduction under small D / d, we newly detected that a synthetic fiber rope also gets strength reduction in the same way. Secondly, we evaluate the strength of various end fixation method of synthetic fiber rope. Knot fixation makes rope strength half in all kinds of knot. Clamping fixation with enough pressuring force can get large strength even if a synthetic fiber rope has low friction coefficient. Although calking fixation and sewing fixation cannot change rope length easily, they can get the largest strength around 85–90% of the rope strength in our experiment. Graphical Abstract: